Optimizing Nitrogen Management in Maize Production:Insights from a Comprehensive Analysis in the US Corn BeltUnder Diverse Climatic Conditions (International Journal of Agriculture and Sustainable Development, 2023)
This academic review delves into the intricate dynamics of nitrogen management in maize production, focusing on the US Corn Belt with an emphasis on cold climates. The study employs a comprehensive approach, utilizing empirical data from the MRTN database, SHAPE framework, and Bayesian regression modeling to analyze Economically Optimal Nitrogen Rates (EONRs) and maize yields. The Adapt-N tool and model simulations further contribute to the exploration of soil health indicators and nitrogen accessibility under varying  climatic conditions. The research reveals a nuanced relationship between temperature, soil organic matter, and nitrogen availability, offering valuable insights for optimizing nitrogen utilization efficiency and minimizing environmental impacts in diverse agricultural settings. The findings underscore the need for adaptive strategies considering the complexities of climate, soil characteristics, and agronomic practices to enhance nitrogen management in maize cultivation.